The association between dietary fiber intake and cognitive function: mediating role of inflammatory markers - Yan, Kaiyun; Wang, Xinshuo; Wang, Fengdan; Chen, Baiyang; Zong, Ziyu; Tian, Jing; Zhao, Jing; Li, Bo (Frontiers in Nutrition, 2025)
AimsCognitive impairment, frequently associated with neurodegenerative diseases such as Alzheimer's disease, may be associated with multiple factors including dietary fiber intake and inflammation. We aimed to explore the associations between reported dietary fiber intake, three novel inflammatory markers, and cognitive function.MethodsThis observational and exploratory cross-sectional study utilized the data from the 2011–2014 of the National Health and Nutrition Examination Survey (NHANES). Digit Symbol Substitution Test (DSST), Consortium to Establish a Registry for Alzheimer's Disease Word Learning (CERAD-WL), CERAD Delayed Recall (CERAD-DR), and Animal Fluency tests (AFT) were used to assess the cognitive function. Linear regression was conducted to explore the relationships between reported dietary fiber intake, three novel inflammatory markers [Albumin-to-alkaline phosphatase ratio (AAPR), Neutrophil-to-Albumin Ratio (NAR), and Systemic Inflammation Response Index (SIRI)] and cognitive function. Mediation analysis was performed to identify the mediating role of inflammatory markers in the relationship between reported dietary fiber intake and cognitive function.ResultsThe final analysis included 2,461 participants. Reported dietary fiber intake was associated with CERAD-WL (β = 0.042, 95% CI = 0.018 to 0.066), AFT (β = 0.060, 95% CI = 0.020 to 0.100) and inflammatory markers (AAPR: β = 0.003, 95% CI=0.002 to 0.004; NAR: β = −0.003, 95% CI = −0.006 to −0.001; SIRI: β = −0.008, 95% CI = −0.015 to −0.001). AAPR was positively associated with WL (β = 1.184, 95% CI = 0.165 to 2.204) and AFT (β = 1.747, 95% CI = 0.229 to 3.264). AAPR mediated the positive association between reported dietary fiber intake and AFT, with mediation proportion of 17.88%.ConclusionsReported dietary fiber intake, inflammatory markers, and cognitive function were pairwise associated. The AAPR played a mediating role in the association between reported dietary fiber intake and cognitive function.